On approximation of maximal operators - Aimar, Hugo Alejandro (2010)
We prove that the weak type (1, 1) boundedness of the maximal of a sequence of integral operators on a metric measure space X follows from the uniform weak type on Dirac deltas of the restriction of the operators to a sequence of approximations of X.